Analisis Kesalahan Kaidah dalam Berbicara Bahasa Arab di Masyarakat Indonesia - Nurul Fahmi (Kilmatuna: Journal Of Arabic Education, 2021)
This study aims to describe the grammar mistakes of Arabic speaking done by Indonesian people. This research uses a type of qualitative describtive research. The source of the data in this study are public in Beji village Jenu sub-district in Tuban districts who make a speech in Indonesia language and often deliver the Arabic words and Arabic sentences. The instrument used in this research include non-systematic observation. Analytical techniques used in analizing language mistakes is qualitative data analysis techniques. The results of this research show that there are grammar errors in Arabic speaking which include; tarkib na’ti, mufrad-jama’, mudzakar-mu’annats, jumlah ismiyah, isim maf’ul, tarkib idlafi, and nakirah-marifat. The advice of this research for the Arabic scholars and the muslims orators in order to use these results as reflection and reference material to be delivered for general public.